A plasmonic lens based on coordinate transformation. Issue 21 (14th December 2020) - Gu, Qiongchan; Li, Yafei; Hu, Chunhai; Lv, Jiangtao; Ying, Yu; Jiang, Xiaoxiao; Si, Guangyuan
Abstract : With the development and maturity of nanofabrication technology, many nanostructures with specific electromagnetic characteristics and optical functions have been designed and demonstrated. Artificial materials with these special optical properties are known as metamaterials. In this paper, a metamaterial lens is proposed and characterized. After using the space transformation approach based on the coordinate transformation principles, the lens becomes anisotropic and inhomogeneous, thus realizing the regulation of electromagnetic waves. The electromagnetic wave transformation characteristics of the superlens are numerically analysed by irradiating a plane transverse wave with a wavelength of 300 nm onto a rectangular slab. The results show that the waveform of the incident light changes from plane waves to cylindrical after passing through the superlens. The validity of the superlens is verified by finite element method calculations.